Fuzzy Bang-Bang Control Scheme of USSC for Voltage Sag Mitigation Due to Short Circuits and Induction Motor Starting in Distribution System - Mohammad Mohammadi; Ashkan Mohammadi Rozbahani; Saman Abasi Garavand; Mahdi Montazeri; Hamed Memarnezhad (Institute of Advanced Engineering and Science, 2014)
Unified series shunt compensator (USSC) has been widely used to mitigate various power quality disturbances in distribution network. The USSC is almost similar to the UPFC, but the only differences are that the UPFC inverters are in shunt series connection and used in transmission systems whereas the USSC inverters are in series-shunt connection and used in distribution systems. USSC, it is possible to compensate a different power quality problem as compared to DSTATCOM and DVR. It is noted that, mitigated load voltage by the DVR is lower than mitigated value obtained by USSC. In other words the USSC can mitigate voltage sag better in compared to DVR and D-STATCOM. Also in case of voltage flicker, unbalance and harmonics elimination it is much effective. Similarly, D-STATCOM is unable to control power flow. It is seen that the proposed USSC can mitigate variety of power quality (PQ) problems. Hence due to multi capability of USSC in power quality improvement, this paper presents the scheme based on fuzzy bang-bang control for USSC. Using Fuzzy Logic Control (FLC) based on bang-bang control; the USSC will contribute to improve voltage sag without deteriorating the effect of the other compensating devices.DOI: http://dx.doi.org/10.11591/ijpeds.v4i4.6254